2007
DOI: 10.1037/0012-1649.43.5.1239
|View full text |Cite
|
Sign up to set email alerts
|

European American and Chinese parents' responses to children's success and failure: Implications for children's responses.

Abstract: The authors examined cultural differences in parents' responses to their children's performance. In Study 1 (N = 421), Chinese 5th graders reported that their parents de-emphasized their academic success and emphasized their academic failure, whereas their American counterparts reported that their parents did the opposite. This partially accounted for Chinese (vs. American) children responding less positively to success and more negatively to failure. In Study 2 (N = 128), Chinese and American mothers' respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
167
3
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(178 citation statements)
references
References 98 publications
7
167
3
1
Order By: Relevance
“…Though parents of different cultures may vary in their patterns of emotional expression (Camras, Chen, Bakeman, Norris, & Cain, 2006;Ng, Pomerantz, & Lam, 2007;Parker et al, 2012), the effects of parents' emotional expression on children's development appear to be consistent across cultures (S. H. Chen, Zhou, Eisenberg, Valiente, & Wang, 2011;Eisenberg, Liew, & Pidada, 2001).…”
mentioning
confidence: 99%
“…Though parents of different cultures may vary in their patterns of emotional expression (Camras, Chen, Bakeman, Norris, & Cain, 2006;Ng, Pomerantz, & Lam, 2007;Parker et al, 2012), the effects of parents' emotional expression on children's development appear to be consistent across cultures (S. H. Chen, Zhou, Eisenberg, Valiente, & Wang, 2011;Eisenberg, Liew, & Pidada, 2001).…”
mentioning
confidence: 99%
“…Hence, variability due to such factors as the type or difficulty of schoolwork is minimized; some studies also control children and parents' perceptions of how good children are at the task (e.g., Ng et al 2007). However, such standardization can also be a drawback as it creates an artificial situation.…”
Section: Other Approaches: Daily Reports and Behavioral Observationsmentioning
confidence: 96%
“…Trained observers who do not have prior ties to the family code parents' actual behavior, thereby permitting heightened objectivity. In this vein, Ng et al (2007) had trained observers code mothers' involvement as manifest in teaching children how to solve the problems on the Raven's Progressive Matrices, checking children's work on the problems, looking at the problems to see what they were like, doing the problems themselves, and paying attention when children showed them the problems. However, more often, investigators have capitalized on the heightened objectivity of behavioral observations, as well as the detailed level of analysis permitted by this method, to assess the quality of parents' involvement, which is rarely assessed in parents, children, and teachers' retrospective reports (for some exceptions, see, Ginsburg and Bronstein 1993;Gottfried et al 1994).…”
Section: Other Approaches: Daily Reports and Behavioral Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported that Japanese children showed less shame and sadness in response to failures, and less pride and more exposure embarrassment in response to success than American children. Moreover, Ng, Pomerantz, and Lam (2007) reported that when school-aged children failed at a task, East Asian parents emphasize the importance of making progress, whereas American parents focused on success.…”
mentioning
confidence: 99%